Relevance of the Concentrations and Sizes of Oligomeric Red Wine Pigments to the Color Intensity of Commercial Red Wines - Juuso Erik Laitila; Juha-Pekka Salminen (American Chemical Society, 2022)
Color is a major sensorial characteristic of red wines. Numerous monomeric and some small oligomeric pigments have been characterized from red wines but the contribution of larger oligomeric pigments to the color intensity has not been established by direct measurements. We measured the color intensity of 317 commercial red wines and semiquantified the malvidin glycosides and eight different adduct groups derived from the malvidin glycosides by ultra-performance liquid chromatography-tandem mass spectrometry. Two of these groups were oligomeric pigments consisting of proanthocyanidins and malvidin glycosides with either direct or methylmethine linkages. The carboxypyranomalvidins and the oligomeric pigments were found to be major contributors to the color intensity. Besides the concentrations, the sizes of the oligomeric pigments had a positive and significant connection to the color intensity. The 1-year-old wines were studied separately and, even in the youngest of wines, the adducts of the malvidin glycosides were the major contributors to the color intensity.